A systematic review of common landmarks in navigated endoscopic sinus surgery (NESS) - Tomislav Baudoin (Taylor & Francis Group, 2021)
Background Navigation brought about a tremendous improvement in functional endoscopic sinus surgery (FESS). When upgraded accordingly, FESS becomes navigated endoscopic sinus surgery (NESS). Indications for intraoperative use of navigation can be broadened to almost any FESS case. NESS in advanced sinus surgery is currently still not used routinely and requires systematic practice guidelines. Purpose The purpose of this paper is to report on commonly identified landmarks while performing advanced NESS according to evidence-based medicine (EBM) principles. Material and methods This review paper has been assembled following PRISMA guidelines. A PubMed and Scopus (EMBASE) search on anatomical landmarks in functional endoscopic and navigated sinus surgery resulted in 47 results. Of these, only 14 (29.8%) contained original data, constituting the synthesis of best-quality available evidence. Results Anatomical landmarks are considered to be the most important points of orientation for optimal use of navigation systems during FESS surgery. The most commonly identified significant landmarks are as follows: (1) Maxillary sinus ostium; (2) Orbital wall; (3) Frontal recess; (4) Skull base; (5) Ground lamella; (6) Fovea posterior; (7) Sphenoid sinus ostium. Conclusions: Establishing common landmarks are essential in performing NESS. This is true for advanced and novice surgeons alike and offers a possibility to use navigation systems systematically, taking advantage of all the benefits of endoscopic navigated surgery.